KAJIAN SITIRAN TERBITAN BERKALA PADA KEGIATAN RISET MINYAK DAN GAS BUMI YANG TEREKAM MEDIA TERAKREDITASI (CITATION STUDY OF OIL AND GAS RESEARCH ACTIVITIES RECORD IN PERIODICAL MEDIA ACCREDITATION) - Himawanto, Himawanto (BACA: Jurnal Dokumentasi dan Informasi, 2015)
Business activities of national oil and natural gas plays an important role because it influences a lot of research that yielded helpful innovative products and scientific research results should be recorded for publication through a reputable publication. Jurnal Scientific Contribution Oil and Gas as media accredited have been choosen researchers to disseminate their research products. Urgent known quality of a scientific paper research results through journal citation reliable indicator. Citation analysis used to explore the practice of journal presence in the bibliography in order to determine the usefulness level, characteristics, and power of citation. During 2010 - 2014 researchers cite 234 journal titles that majority coming from abroad. Journal cited generally have a conventional shape and obtained paid. Citation itself tends bit and gas technology research group active cites. Then from the mapping results obtained emergence total approaching journal article citation frequency. Common characteristics are evaluated is realized through collaboration, have reasonable degree of sophistication, produced from United States, write in English, and indexed by Scopus. Citation strongest by title of article found in similar journals, while “Taber JJ” is influential writer. Aggressive authors cite journal played by Oberlin Sidjabat and Morina from research center, then Imansyah Ibnu Hakim from college.